Osteosarcopenia predicts greater risk of functional disability than sarcopenia: a longitudinal analysis of FraDySMex cohort study - Oscar Rosas-Carrasco; Betty Manrique-Espinoza; Juan Carlos López-Alvarenga; Beatriz Mena-Montes; Isabel Omaña-Guzmán (Elsevier, 2024)
Objectives: Aging involves significant changes in body composition, marked by declines in muscle mass and bone mineral density alongside an increase in fat mass. Sarcopenia is characterized by low strength and muscle mass, and osteosarcopenia is the coexistence of sarcopenia and osteopenia/osteoporosis. Physiologically, there is a crosstalk between muscle and bone tissues mediated by several pathways. Both, sarcopenia and osteosarcopenia, have been related with adverse outcomes such as functional disability. However, there is a lack of longitudinal studies. Therefore, this study aimed to assess whether sarcopenia and osteosarcopenia phenotypes increased the risk of functional disability in a longitudinal cohort of community-dwelling adults. Design: This study constitutes a secondary longitudinal analysis of data derived from the prospective cohort FraDySMex (Frailty, Dynapenia, and Sarcopenia in Mexican adults). Setting and participants: FraDySMex is conducted in community-dwelling adults aged 50 years or older living in Mexico City. Data from 2014 to 2015 was considered as baseline evaluation, and the 2019 wave was the follow-up evaluation. Individuals with complete baseline and follow-up evaluations were included in the analysis. Measurements: Sarcopenia diagnosis adhered to the FNIH criteria, while osteopenia/osteoporosis classification followed WHO guidelines. Osteosarcopenia was defined as the concurrent presence of sarcopenia and osteopenia/osteoporosis. Functional disability was identified by the Lawton Instrumental Activities of Daily Living (IADL) Scale. Adjusted mixed-effects logistic regression models were estimated to evaluate the effect of body composition phenotype on the risk of functional disability. Results: The final sample included 320 adults with complete longitudinal data. The majority of were women (83.4%) and had 7-12 years of education (48.4%). At the baseline evaluation, 50.9% aged 50-70. The osteosarcopenia phenotype was associated with a higher risk of functional disability (OR: 2.17, p = 0.042) compared with the no osteopenia/sarcopenia group. Conversely, sarcopenia (OR: 1.50, p = 0.448) and osteopenia/osteoporosis (OR: 1.50, p = 0.185) phenotypes were not associated with functional disability. Conclusions: Our study underscores that osteosarcopenia significantly increased the risk of functional disability, particularly in terms of Instrumental Activities of Daily Living (IADL). These results emphasize the importance of screening for sarcopenia, osteopenia/osteoporosis, and osteosarcopenia across various clinical settings. Early detection and intervention hold promise for averting functional disability and mitigating associated adverse outcomes in adults.